Transformasi Branding Kota Cimahi Sebagai Kota Kreatif - Nada Arina (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2014)
Abstract: This research used qualitative approach with the constructivism paradigm and case study form of study. The subject were Cimahi government officials and businessmen who are members of the entrepreneurial community in Cimahi which were purposively selected. Data were collected through in in depth interview, passive participant observation. The result of this research revealed that background of Transformation Branding Creative City Cimahi as seen from the absence of territory and natural resources, abundant potential of human and creative products, based on center government regulations and the city as well as a declining manufacturing industry. While the background of the local Economic Development in an effort to realize the Creative City is the quickness of cooperation and participation of government and society, develop the local economy Cimahi, the lack of communication channels to between entrepreneurs, business people and government, no previous systematic development, assistance from organizations world, and the launching of the program of the government. The understanding of the relevant parties regarding the Transformation Branding Cimahi as a creative city, seen from the understanding of the campaign, understanding local Economic Development (LED) program in an effort to realize the Creative City, the campaign goal, and uniqueness of Cimahi. While government programs Cimahi city and related agencies in supporting the transformation of city branding Creative Cimahi as the city is divided into 3 phases, namely planning, execution and evaluation. Communication patterns Cimahi city government and relevant agencies to promote the transformation of city branding Cimahi as Creative cities are categorized into two, namely to businesses as the primary and the general public. Abstrak: Pendekatan penelitian yang digunakan adalah kualitatif, dengan paradigma konstruktivisme, dan jenis studi kasus. Subjek penelitiannya adalah aparatur Pemerintah Kota Cimahi serta pelaku usaha yang tergabung di komunitas kewirausahaan di Cimahi yang dipilih secara purposif. Pengumpulan data diperoleh melalui wawancara mendalam, observasi partisipan pasif, dan studi pustaka. Hasil penelitian mengungkapkan bahwa: latar belakang Transformasi Branding Kota Cimahi sebagai Kota Kreatif dilihat dari ketiadaan wilayah dan SDA, potensi SDM yang melimpah dan produknya yang kreatif, berdasarkan peraturan pemerintah pusat dan kota serta industri manufaktur yang menurun. Sedangkan latar belakang Pengembangan Ekonomi lokal sebagai upaya untuk mewujudkan Kota Kreatif adalah butuhnya kerjasama dan partisipasi pemerintah dan masyarakat, menumbuhkembangkan ekonomi lokal Cimahi, tidak adanya saluran komunikasi untuk antara antara pelaku usaha, pelaku usaha dan pemerintah, pengembangan terdahulu yang tidak sistematis, bantuan dari organisasi dunia, dan pencanangan program dari pemerintah. Adapun pemahaman pihak-pihak terkait mengenai Transformasi Branding Kota Cimahi sebagai Kota kreatif, dilihat dari pemahaman kampanye, pemahaman program Pengembangan Ekonomi lokal (PEL) dalam upaya mewujudkan Kota Kreatif, Tujuan kampanye, dan keunikan Kota Cimahi. Sedangkan program-program pemerintah kota Cimahi dan dinas-dinas terkait dalam mendukung upaya transformasi branding kota Cimahi sebagai kota Kreatif terbagi atas 3 fase, yaitu perencanaan, eksekusi dan evaluasi. Pola-pola komunikasi yang dilakukan pemerintah kota Cimahi dan dinas-dinas terkait untuk mensosialisasikan transformasi branding kota Cimahi sebagai kota Kreatif dikategorikan menjadi dua, yaitu kepada pelaku usaha sebagai target utama dan masyarakat umum.